Activation of Basophils Is a New and Sensitive Marker of Biocompatibility in Hemodialysis. Issue 11 (9th April 2014) - Aljadi, Zenib; Mansouri, Ladan; Nopp, Anna; Paulsson, Josefin M.; Winqvist, Ola; Russom, Aman; Ståhl, Mårten; Hylander, Britta; Jacobson, Stefan H.; Lundahl, Joachim
Abstract The hemodialysis procedure involves contact between peripheral blood and the surface of dialyzer membranes, which may lead to alterations in the pathways of innate and adaptive immunity. We aimed to study the effect of blood–membrane interaction on human peripheral basophils and neutrophils in hemodialysis with high‐ and low‐permeability polysulfone dialyzers. The surface expression of CD203c (basophil selection marker) and CD63 (activation marker) after activation by the bacterial peptide formyl‐methionyl‐leucyl‐phenylalanine (fMLP) or anti‐Fcε receptor I (FcεRI) antibody and the absolute number of basophils was investigated before and after hemodialysis with each of the dialyzers. Moreover, the expression on neutrophils of CD11b, the CD11b active epitope, and CD88 was analyzed in the same groups of individuals. The expression of CD63 in basophils following activation by fMLP was significantly higher in the patient group compared with that in healthy controls, but no differences were observed after activation by anti‐FcεRI. During the hemodialysis procedure, the low‐flux membrane induced up‐regulation of CD63 expression on basophils, while passage through the high‐flux membrane did not significantly alter the responsiveness. In addition, the absolute number of basophils was unchanged after hemodialysis with either of the dialyzers and compared with healthy controls. We found no significant differences in the expression of the neutrophil activation markers (CD11b, the active epitope of CD11b, and CD88) comparing the two different dialyzers before and after dialysis and healthy controls. Together, these findings suggest that alterations in basophil activity may be a useful marker of membrane bioincompatibility in hemodialysis.